Analysis of adipose tissue immune gene expression after vaccination of rainbow trout with adjuvanted bacterins reveals an association with side effects. (August 2017) - Veenstra, Kimberly A.; Wang, Tiehui; Alnabulsi, Ayham; Douglas, Alex; Russell, K. Spencer; Tubbs, Lincoln; Arous, Juliette Ben; Secombes, Christopher J.
Highlights: Trout adipose is a sensitive tissue for studying adjuvant effects. Relationship between adipose tissue immune function and vaccine induced adhesions. Large number of immune genes upregulated in adipose over time in response to vaccines. Immune gene profile in adipose can potentially predict visible side effects. Trout adipose is an important immune tissue with a possible regulatory role. Abstract: Most existing fish vaccines are presented in the form of oil-based emulsions delivered by intraperitoneal injection. Whilst very effective they are frequently associated with inflammatory responses that can result in clinically significant side-effects often involving the adipose tissue that is in direct contact with the vaccine. To explore the potential of immune gene expression changes in the adipose tissue of fish to be markers of vaccination efficacy or development of side-effects we have studied the response to a bacterial ( Aeromonas salmonicida ) vaccine administered with two different adjuvants. The first adjuvant was Montanide™ ISA 763A VG, thought to induce a mostly humoral response, and the second was Montanide™ ISA 761 VG that gives a more balanced humoral and cell mediated response. Following vaccination tissue samples were collected at days 3, 14 and 28 for RTqPCR analysis. Fifty immune genes were studied with a focus on a) pro-inflammatory associated molecules and b) adaptive immune response related molecules linked with possible Th1, Th2, Th17 and T-regulatory pathways, with the expression data analysed for associations with Speilberg post-vaccination side effect scores. The results showed that the adipose tissue is a particularly sensitive and discriminatory tissue for studying adjuvant effects. A clear upregulation of many immune genes occurred in response to both vaccine groups, which persisted over time and overlapped with the appearance of visible adhesions. Our analysis revealed a relationship between adipose tissue immune function and the development of vaccine-induced adhesions giving the potential to use immune gene expression profiling in this tissue to predict the side-effects seen.